Machine learning bookcamp - Grigoriev, Alexey (Manning Publications, 2021)
The best hands-on guide to begin your machine learning journey. Gustavo Filipe Ramos Gomes, Troido Time to flex your machine learning muscles! Take on the carefully designed challenges of the Machine Learning Bookcamp and master essential ML techniques through practical application. In Machine Learning Bookcamp you will: Collect and clean data for training models Use popular Python tools, including NumPy, Scikit-Learn, and TensorFlow Apply ML to complex datasets with images Deploy ML models to a production-ready environment The only way to learn is to practice! In Machine Learning Bookcamp, you'll create and deploy Python-based machine learning models for a variety of increasingly challenging projects. Taking you from the basics of machine learning to complex applications such as image analysis, each new project builds on what you've learned in previous chapters. You'll build a portfolio of business-relevant machine learning projects that hiring managers will be excited to see. about the technology Master key machine learning concepts as you build actual projects! Machine learning is what you need for analyzing customer behavior, predicting price trends, evaluating risk, and much more. To master ML, you need great examples, clear explanations, and lots of practice. This book delivers all three! about the book Machine Learning Bookcamp presents realistic, practical machine learning scenarios, along with crystal-clear coverage of key concepts. In it, you'll complete engaging projects, such as creating a car price predictor using linear regression and deploying a churn prediction service. You'll go beyond the algorithms and explore important techniques like deploying ML applications on serverless systems and serving models with Kubernetes and Kubeflow. Dig in, get your hands dirty, and have fun building your ML skills! about the audience Python programming skills assumed. No previous machine learning knowledge is required. about the author Alexey Grigorev is a principal data scientist at OLX Group. He runs DataTalks. Club, a community of people who love data. Great theory, real-life examples, and just the right amount of code. An absolute feast for a beginner who wants to enter the realm of machine learning. Krishna Chaitanya Anipindi, Hexagon A practical guide for anyone aspiring to be a data scientist. Amaresh Rajasekharan, IBM Corporation Exactly the practice I needed to be comfortable with machine learning. Nathan D'Elboux, Isparex NARRATED BY ADAM NEWMARK.